Pelatihan Menulis Artikel Ilmiah berbasis Service Learning untuk Guru Sekolah Dasar - Rizqi Putri Nourma Budiarti; Afib Rulyansah; Emy Yunita Rahma Pratiwi; Destita Shari (Indonesia Berdaya, 2022)
One of the abilities that educators don't often get much training in is how to write scientific articles. The explanation for this is because the instructors have received inadequate training to write scientific articles. At the moment, one of the necessary criteria for instructors to fulfill in order to advance their careers is the publication of scholarly publications. The purpose of this community service project is to provide assistance to educators in the process of creating scholarly publications that are based on the findings of classroom action research (CAR) that has been completed. Workshops, roundtable discussions, question-and-answer sessions, in-person counseling sessions, and e-mail correspondence were all integral parts of the methodology. The findings pointed to a paradigm change in the way that scientific papers are written. After going through the training, the instructors were able to overcome the challenges they had encountered in the beginning. This was due to the fact that they were now aware of how to incorporate the findings of the CAR into article writing. According to the findings, more training and direction had a positive effect on the instructors' ability, and the drafts were generally satisfactory with room for advancement. After that, the papers will be submitted to respected publications with the intention of advancing the instructors' careers.  Abstrak: Salah satu kemampuan yang seringkali tidak banyak dilatih oleh pendidik adalah bagaimana menulis artikel ilmiah. Penyebabnya adalah karena para guru belum mendapatkan pelatihan yang memadai untuk menulis artikel ilmiah. Saat ini, salah satu kriteria yang harus dipenuhi oleh para pengajar untuk memajukan karir mereka adalah publikasi publikasi ilmiah. Tujuan dari proyek pengabdian masyarakat ini adalah untuk memberikan bantuan kepada para pendidik dalam proses pembuatan publikasi ilmiah yang didasarkan pada temuan penelitian tindakan kelas (PTK) yang telah diselesaikan. Lokakarya, diskusi meja bundar, sesi tanya jawab, sesi konseling langsung, dan korespondensi email adalah bagian integral dari metodologi. Temuan menunjukkan perubahan paradigma dalam cara penulisan karya ilmiah. Setelah melalui pelatihan, para guru mampu mengatasi tantangan yang mereka temui di awal. Pasalnya, mereka kini sudah paham bagaimana memasukkan temuan PTK ke dalam penulisan artikel. Menurut temuan, lebih banyak pelatihan dan arahan memiliki efek positif pada kemampuan guru, dan konsep umumnya memuaskan dengan ruang untuk kemajuan. Setelah itu, makalah akan diserahkan ke publikasi terkemuka dengan tujuan memajukan karir guru.